-2+7=6-(9p+7)

Simple and best practice solution for -2+7=6-(9p+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+7=6-(9p+7) equation:


Simplifying
-2 + 7 = 6 + -1(9p + 7)

Combine like terms: -2 + 7 = 5
5 = 6 + -1(9p + 7)

Reorder the terms:
5 = 6 + -1(7 + 9p)
5 = 6 + (7 * -1 + 9p * -1)
5 = 6 + (-7 + -9p)

Combine like terms: 6 + -7 = -1
5 = -1 + -9p

Solving
5 = -1 + -9p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '9p' to each side of the equation.
5 + 9p = -1 + -9p + 9p

Combine like terms: -9p + 9p = 0
5 + 9p = -1 + 0
5 + 9p = -1

Add '-5' to each side of the equation.
5 + -5 + 9p = -1 + -5

Combine like terms: 5 + -5 = 0
0 + 9p = -1 + -5
9p = -1 + -5

Combine like terms: -1 + -5 = -6
9p = -6

Divide each side by '9'.
p = -0.6666666667

Simplifying
p = -0.6666666667

See similar equations:

| 2v-8=-12 | | 4(x-1)=x-3 | | 2p+3-4+3= | | 3d^2-17=0 | | 2p+3-4+12=3 | | Y=2*2+-3 | | -7/4y=35 | | 17=5 | | -10x(x+5)+76=-12-12 | | 2p+3-4+5= | | 10x^(1/3) | | 2p+3-4+2= | | 10x^1/3 | | -3=-5(4x+2)+21x | | 2p+3-4+1= | | 2p+3-4+10= | | 9f-1=4(2f-1)-4(-5+f) | | 2p+3-4+6= | | -4a+16+6a=7a-9a | | 2p+3-4+11= | | -3/4x-5=10 | | -6x-1=-73 | | 1/4x+3=x | | 9-2x+14=13 | | 2p+3-4+12= | | X+3.48=6.14 | | -19-(-45)=x/2 | | -5(b+8)=-7(b+2) | | 0.3x-0.7x-19=1 | | 2.6=-0.2t | | m+12=26 | | 2(4c-1)-6=5c+4 |

Equations solver categories